KEFAHAMAN DAN SAMBUTAN TERHADAP KOD ETIKA ISLAM: PENGALAMAN TABUNG HAJI - Kamri, Nor ’Azzah (Jurnal Syariah, 2019)
Islamic code of ethics plays a significant role in an organization. It contributes in developing an ethical working culture in the organization. This article examines the understanding and response of Tabung Haji staff towards implementation actions taken by Tabung Haji management in implementing Islamic ethics in its organization. The findings show that the implementation actions were well-understood, well-accepted and well-practiced among respondents in their work. Nevertheless, problems faced by respondents show that aggressive action should be taken to enhance the practice of Islamic ethics in the organization.